PENGARUH KEPUASAN DAN KEPERCAYAAN MASYARAKAT (PESERTA) TERHADAP PENERAPAN APLIKASI MOBILE JKN - Yani, Riska Putri; Indriani, Wiewiek; Rahyono, Rahyono (Jurnal Jejama Manajemen Malahayati, 2023)
This study means to decide if there is a significantl influence between satisfaction and public trust in the role of the JKN mobile application. The sample used 100 people. The researc method used is the library method and the field method including (Observation, Interview, Questionnaire, and Documentation). The analytical tools used are Validity, Reliability, Normality, Numerous Straight Relapse by utilizing Speculation Testing, in particular T Test, F Test, and Coefficient of Assurance Test (R2).The resultls showed that partially and simultalneously the variables of Satisfaction and Trust had a signifilcant effect on the Cellular JKN Application Variables.